Cumulative fault throw measurements from topographic profiles (from 2 m resolution DEM) and measured throws from 2016 coseismic ruptures of the Mt.Vettore-Mt.Bove Fault System (central Italy) - Irene Puliti; Alberto Pizzi; Lucilla Benedetti; Alessandra Di Domenica; Jules Fleury (PANGAEA, 2020)
The dataset compiles measurements of fault throw displacements of coseismic ruptures produced after the 2016 seismic events in central Italy (T2); measurements of fault throw displacements of cumulative morphological fault scarp (T1) and slip vector data (T3). The dataset contains label code for each measurement, geographic information (Easting and northing coordinates), and offsets as measured by topographic profiles extracted from digital elevation model topography from satellite Pleiades images provided by the Centre national d extquotesingleétudes spatiales (CNES) (ISIS and CEOS_seismic pilot (ESA) programs).